PEMBERDAYAAN MASYARAKAT MELALUI EXPERIENTIAL ECOTOURISM BERBASIS ABCD DI DESA SIGEDANG, WONOSOBO - Jumiati Ningsih; Rafly Satria; Nadina Nazwa Dwiningtias; Azizahtun Naviah (Jurnal Pengabdian Masyarakat : BAKTI KITA, 2026)
Sigedang Village has abundant coffee and vegetable agrotourism potential at the foot of Mount Sindoro, but its management has not been optimally integrated. This community service program aims to empower the community, especially the Youth Organization (Karang Taruna), in developing ecotourism through an Asset-Based Community Development (ABCD) approach. The methods used include participatory asset mapping, in-depth interviews, and assistance in digital content creation. The results of the activity show that through an experiential ecotourism strategy, village assets in the form of agricultural activities can be packaged into a systematic "Trekking KEWONO" tour package. In addition, strengthening digital branding through documentary videos has been proven to increase the confidence of local youth in managing village potential. The conclusion of this activity is that effective empowerment must place the community as the main subject to ensure economic sustainability and environmental conservation.